IMPLEMENTASI PERATURAN DAERAH NOMOR 4 TAHUN 2008 TENTANG SISTEM PELAYANAN AIR MINUM DI KECAMATAN TAYAN HILIR KABUPATEN SANGGAU - Dessi Ariyanti E.01106058 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This thesis is intended to provide input to the PDAM services in accordance with its founding mission and purpose is as a service provider of clean water for the community, the service is not only seen on the quantity but also in quality, namely the provision of quality water services and reach out to the whole community can running optimally in accordance with the Regional praturan No. 4 of 2008 on Service System taps in the District Hilir Subdistrict Tayan. Keywords: Implementation Regulation, Ministry taps